Formulation of Body Lotion Ethanol Extract of Kepundung Bark (Baccaurea Macrocarpa (Miq.) Mull Arg.) and Antioxidant Activity Test - Noni Rahayu Putri; Tisa Mandala Sari; Sri Rahma Z (Universitas Ahmad Dahlan, 2025)
The bark of kepundung (Baccaurea macrocarpa (Miq.) Mull Arg.) contains secondary metabolite compounds from polyphenols such as flavonoids, phenolic, terpenoids, and alkaloids, which have the potential for natural antioxidants. This research aims to evaluate of ethanol extract from kepundung bark and formulate the body lotion to test its antioxidant activity using the DPPH method. Body lotion formulas were made with variations in the concentration 0.4, 1.0, and 1.6% of ethanol extract of kepundung bark as active ingredients. The evaluation of body lotion included organoleptic, pH, homogeneity, type of body lotion, stability, viscosity, irritation, and antioxidant activity tests. The results of the physical evaluation of the body lotion meet the requirements. Namely, all formulas are homogeneous, according to skin pH, the viscosity of the preparation ranges from 2500 cP, stable, and does not irritate. The value IC50 antioxidant activity of ethanol extract of kepundung bark was 4.04 ppm. The value IC50 antioxidant activity body lotion at F1, F2, and F3 respect 41.91, 36.98, and 33.13 ppm. The result showed the best formula is F3 with a value IC50 33.13 ppm. Based on the study, the ethanol extract of depending bark and the body lotion has very strong antioxidant activity.